The story of a knowledge-based and learning organization - Jan Hjelte; Kristina Westerberg (Nordic Journal of Social Research)
Knowledge is generally viewed as one of the most important organizational resources, and this view is also held in relation to municipal elderly-care organizations. However, the concept of a knowledge-based organization has seldom been addressed in elderly-care research. The aim of the present study was to analyse how political and professional groups involved in elderly care conceive of the idea of a knowledge-based organization, and how these conceptions relate to their expectations in relation to the future of elderly care. This issue is important because these conceptions are intertwined with actions conducted by organizational members. Participants were selected for the study on the basis of organizational level and engagement in the development of different kinds of care in an elderly-care organization in a large municipality. A narrative approach was used for data analysis. The study indicates that the interpretations of a knowledge-based organization bring stability and meaning to participants by linking elderly care, as it is in the present, to an image of its future. Furthermore, the narratives are adjusted depending on what kind of problems that organization is expected to solve. However, the participants do not view the economic resources of the organization as something they can influence and develop, in either the present or the future. The study also shows that there are multiple perspectives in regard to the meaning of a knowledge-based organization and, accordingly, multiple perspectives on what will need to be done in the future. This is a potential problem for elderly care because it can hinder the coordination of organizational activities and the ability to handle the challenges of the future. Therefore the results point to the importance of creating within the organization a shared meaning of its main problems, and to the contribution a knowledge-based organization can make in solving these problems.